2014
DOI: 10.1016/j.seizure.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

A community study in Cornwall UK of sudden unexpected death in epilepsy (SUDEP) in a 9-year population sample

Abstract: This study is the first epidemiological study in England occurring in a whole population identifying systemically all deaths and the first large scale review in UK of SUDEP deaths since 2005. Being a community based study a key issue which was highlighted was that in the SUDEPs examined many might have been potentially preventable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 29 publications
3
42
1
Order By: Relevance
“…Their comments are in line with those of some health professionals who suggest that some epilepsy deaths may be preventable with appropriate guidance and care [23][24][25][26][27][28][29]. Such a goal involves quality informed medical support [24,25], optimisation of seizure control and patient education for self-management.…”
Section: Sub-themes Example Of Commentssupporting
confidence: 59%
“…Their comments are in line with those of some health professionals who suggest that some epilepsy deaths may be preventable with appropriate guidance and care [23][24][25][26][27][28][29]. Such a goal involves quality informed medical support [24,25], optimisation of seizure control and patient education for self-management.…”
Section: Sub-themes Example Of Commentssupporting
confidence: 59%
“…Ninety three deaths were thus identified by the coroner's office. Each death's case file which included all comprehensive medical records up to the point of death was reviewed to ascertain those deaths which met the SUDEP criteria and classification using the operational definition of SUDEP provided by Nashef and Anneger 4,8 We calculated the odds ratio for having a specific factor in those who died from SUDEP compared to controls. We ranked the factors according to P value and used a sequential Bonferroni to correct for multiple comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…These 20 factors were subsequently applied to a previously unexposed set of all SUDEPs (n=48) extracted by going through all epilepsy deaths (n=93) in the county of Cornwall UK (population 550,000) between 2004 -2012 to see if they remained consistent with the literature review findings 4 . It was found that 17 factors remained well associated with SUDEP and are directly relevant for people living with epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…However the presence of a specialist ID epilepsy service in Cornwall could have influenced the results significantly. 33 The second phase of the literature review considered the country of origin and the type of healthcare associated with that country (Table 3).…”
Section: Resultsmentioning
confidence: 99%